Strategies for Enhancing Early Childhood Science Literacy Through STEAM Education - M.A Muazar Habibi (Jurnal Penelitian Pendidikan IPA, 2023)
The primary objective of this study is to enhance young children's comprehension of scientific concepts by implementing the STEAM approach within the context of Early Childhood Education (PAUD). The STEAM (Science, Technology, Engineering, Art, and Mathematics) pedagogy for preschoolers emphasizes dynamic learning, stimulates cognitive engagement, facilitates problem-solving, nurtures structured and methodical reasoning, and enhances critical thinking skills. Conducted using the Classroom Action Research method guided by the Kemmis cycle model, this study involves a cohort of 15 participants from group B, aged 5-6 years, and spans across preliminary cycles, Cycle I, and Cycle II, comprising phases of planning, execution, observation, and reflection. The comprehensive deliberation's outcome establishes the potential for enhancing scientific literacy among young children through the implementation of STEAM education. This advancement in scientific understanding is facilitated through captivating balloon experiments, utilizing colors that resonate with children's preferences. The attainment of scientific knowledge, as evident through the STEAM approach, manifests at a rate of 10% during the Pre-Cycle, 26% during Cycle I, and an impressive 72% during Cycle II. The cumulative findings unequivocally underscore the profoundly positive role of STEAM pedagogy in augmenting scientific cognizance during the formative years of early childhood.